Gradient in excitation-contraction coupling in canine gastric antral circular muscle. - Bauer, A J (1985)
Slow waves decay in amplitude as they propagate through the thickness of circular muscle of the canine antrum. Slow waves are the excitable events that initiate contractions in the antrum. Excitation-contraction coupling occurs if slow wave depolarizations surpass a 'mechanical threshold'. The amplitude of slow waves recorded from circular muscle cells near the submucosa was insufficient to reach the mechanical threshold previously determined for muscle near the myenteric plexus, suggesting that either submucosal cells are normally mechanically quiescent, or that contractions of submucosal cells are initiated at more polarized levels. Experiments were performed to determine the voltage-tension relationships in adjacent 'myenteric' and 'submucosal' circular muscles. Membrane potentials of the muscles were depolarized by elevated concentrations of potassium. Submucosal muscles were stimulated to contract at lower potassium concentrations than were myenteric muscles. Contractions of submucosal muscles at each potassium concentration studied were more forceful than contractions of myenteric muscles. Plots of membrane potential vs. potassium concentration on a logarithmic scale showed that the membrane potential of myenteric cells was more dependent upon the potassium gradient than the membrane potential of submucosal cells. The potassium permeability of both groups of cells increased when depolarized, and the slopes of these plots approached Nernstian levels when depolarized below -55 mV. Force developed in submucosal strips at more polarized levels than in myenteric muscles. The 'mechanical threshold' of submucosal muscles was 5-10 mV above resting potential, whereas myenteric muscles had to be depolarized by 25-30 mV before contraction was initiated. The mechanisms responsible for the difference in mechanical thresholds are not known, but differences in the voltage dependence of calcium channels, in calcium release mechanisms, or in the sensitivity of the contractile proteins to calcium could be involved.